Gene therapy for retinal dystrophies - Issa, P; Groppe, M; MacLaren, R (2012)
Genetic mutations are the cause of inherited retinal dystrophies. The underlying genetic basis of these diseases suggests that a gene therapy approach is logical either to replace or reduce the expression of defective genes. The first proof-of-concept clinical studies in patients with Leber's congenital amaurosis have suggested that retinal gene therapy is safe and potentially effective, at least for specific disease entities. In contrast to pharmacological treatment gene therapy has the advantage of being able to express a protein within specific cell populations and is a potentially definitive therapy. Besides replacing deficient genes in inherited diseases, additional strategies that might broaden the application of retinal gene therapy are also being developed. These include the permanent expression of neuroprotective substances or photosensitive molecules (so-called optogenetics). This overview discusses the current clinical strategies and potential problems of retinal gene therapy. © 2012 Springer-Verlag.